THE CORRELATION BETWEEN LEARNING STYLE AND STUDENTS' ENGLISH ACHIEVEMENT - Farih, Abdullah; Fatmawaty, Riryn; Nur Indah Sari, Annisa (As-Sulthan Journal of Education, 2026)
The purpose of the study is to determine the correlation between students' learning styles and their English achievement. The research focuses on four learning styles based on the VARK model: Visual, Auditory, Read or Write, and Kinesthetic. A quantitative method with a correlational approach was used, involving eleventh-grade students from one class at a senior high school. The instruments used in this study were a learning style questionnaire consisting of 28 items (7 items for each learning style) and an English achievement test in the form of 30 multiple-choice questions. The data were analyzed using Spearman Rank Correlation to determine the relationship between each learning style and students’ English achievement. The results showed that there was no significant correlation between the four learning styles and students’ English achievement. These findings indicate that learning style preferences may not be strong predictors of students' academic performance in English. Therefore, it is suggested that teachers implement more varied and inclusive teaching strategies that can accommodate different learning preferences and consider other factors that may influence student achievement